Negative electrode material, secondary battery, and electric device

CN123017905APending Publication Date: 2026-10-30BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510592378.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-08
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本申请实施例的目的是提供一种负极材料、二次电池及用电设备,至少解决现有CVD硅碳材料首效偏低的问题

Benefits of technology

[0021]在本申请实施例中,负极材料包括碳基体及分散于碳基体中的纳米硅,碳基体的I值大于等于400A.U.,且Y值大于等于15%;其中,I值为所述碳基体在XRD测试时26.5°的峰强度,Y值为所述碳基体组成扣式电池在首次充电测试后,0.3V以下容量占首次放电容量的比例。通过对碳基体结晶性进行设计,控制碳基体的I值大于等于400A.U.,使得碳基材的结晶性较好,且碳在放电过程中贡献显著,锂离子脱嵌效率较高,能够实现高效可逆储锂,可以在保证硅碳复合结构完整性的前提下显著提升首效,从而突破掺硅电芯能量密度的天花板,满足市场对高性能锂离子电池的迫切需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017905A_ABST
    Figure CN123017905A_ABST
Patent Text Reader

Abstract

The application discloses a negative electrode material, a secondary battery and an electric device. The negative electrode material provided by the application comprises a carbon base and nano-silicon dispersed in the carbon base. The I value of the carbon base is greater than or equal to 400 A.U. The I value is the peak intensity of the carbon base at 26.5° in XRD testing. By designing the crystallinity of the carbon base and controlling the I value of the carbon base to be greater than or equal to 400 A.U., the carbon can contribute significantly in the discharge process, the lithium ion deintercalation efficiency is high, the reversible lithium storage can be realized, the initial efficiency can be significantly improved under the premise of ensuring the integrity of the silicon-carbon composite structure, and thus the energy density ceiling of the silicon-doped battery is broken, and the urgent needs of the market for high-performance lithium ion batteries are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of secondary battery technology, specifically relating to a negative electrode material, a secondary battery, and an electrical device. Background Technology

[0002] With the increasing demand for high-energy-density lithium-ion batteries, silicon-carbon composite anodes have become the core material to replace traditional graphite due to their high specific capacity (>1000mAh / g).

[0003] However, silicon-carbon materials prepared by chemical vapor deposition (CVD) have the problem of low initial efficiency, resulting in a large number of lithium ions being irreversibly lost in the first cycle, which seriously restricts the effective improvement of cell energy density. Summary of the Invention

[0004] The purpose of this application is to provide a negative electrode material, a secondary battery, and an electrical device, which at least solves the problem of low initial efficiency of existing CVD silicon-carbon materials.

[0005] In a first aspect, embodiments of this application provide a negative electrode material, comprising a carbon matrix and nano-silicon dispersed in the carbon matrix, wherein the I value of the carbon matrix is ​​greater than or equal to 400 A.U.;

[0006] Wherein, I value is the peak intensity of the carbon matrix at 26.5° during XRD testing.

[0007] Optionally, in the negative electrode material, the I value is 600 to 1200 A.U.

[0008] Optionally, in the negative electrode material, the carbon matrix is ​​selected from at least one of resin-based, biomass-based, and petroleum coke-based materials.

[0009] Optionally, in the negative electrode material, the particle size of the carbon matrix is ​​5–10 μm.

[0010] Optionally, in the negative electrode material, the mass fraction of the nano-silicon is 10% to 80%.

[0011] Optionally, in the negative electrode material, the mass fraction of the nano-silicon is 30% to 50%.

[0012] Optionally, in the negative electrode material, the Y value of the carbon matrix is ​​greater than or equal to 15%; wherein, the Y value is the proportion of the capacity below 0.3V of the coin cell composed of the carbon matrix (101) to the initial discharge capacity after the first charge test.

[0013] Optionally, in the negative electrode material, the ICE value of the negative electrode material is greater than or equal to 84%, wherein the ICE value is the proportion of the capacity above 0.8V to the initial discharge capacity after the first charge test of the coin cell assembled from the negative electrode material.

[0014] Optionally, in the negative electrode material, the nano-silicon is silicon particles with a particle size of 0-2 nm.

[0015] Secondly, embodiments of this application provide a method for preparing a negative electrode material, comprising:

[0016] The carbon source is heat-treated at a temperature of 800°C or higher for 24 to 240 hours to obtain a carbon matrix.

[0017] Nano-silicon is deposited on the surface of the silicon substrate to obtain the negative electrode material.

[0018] Thirdly, embodiments of this application provide a secondary battery, including a negative electrode sheet, the negative electrode sheet including a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, the negative electrode active material layer including the negative electrode material as described above.

[0019] Fourthly, embodiments of this application provide an electrical device including the aforementioned secondary battery, wherein the secondary battery serves as the power supply for the electrical device.

[0020] Fifthly, embodiments of this application provide a vehicle that includes the electrical equipment described in the third aspect above.

[0021] In this embodiment, the negative electrode material includes a carbon matrix and nano-silicon dispersed in the carbon matrix. The I value of the carbon matrix is ​​greater than or equal to 400 A.U., and the Y value is greater than or equal to 15%. Here, I value is the peak intensity of the carbon matrix at 26.5° during XRD testing, and Y value is the proportion of the capacity below 0.3V in the coin cell formed by the carbon matrix after the first charge test to the first discharge capacity. By designing the crystallinity of the carbon matrix and controlling the I value to be greater than or equal to 400 A.U., the carbon substrate exhibits good crystallinity, and carbon contributes significantly during discharge, resulting in high lithium-ion insertion / extraction efficiency. This enables efficient and reversible lithium storage, significantly improving the first-cycle efficiency while maintaining the integrity of the silicon-carbon composite structure. This breaks through the energy density ceiling of silicon-doped cells, meeting the market's urgent demand for high-performance lithium-ion batteries. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the structure of a negative electrode material provided in an embodiment of this application;

[0023] Figure 2 This diagram illustrates the calculation process of the I value of the carbon matrix in Embodiment 1 of this application.

[0024] Figure label:

[0025] 10: Anode material; 101: Carbon matrix; 102: Nano-silicon. Detailed Implementation

[0026] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0027] The terms "first" and "second" in the specification and claims of this application may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise stated, "multiple" means two or more. Furthermore, "and / or" in the specification and claims indicates at least one of the connected objects, and the character " / " generally indicates that the preceding and following objects are in an "or" relationship.

[0028] Among related technologies, silicon-carbon materials prepared by chemical vapor deposition (CVD) have the problem of low initial efficiency, resulting in a large number of lithium ions being irreversibly lost in the first cycle, which seriously restricts the effective improvement of the cell's energy density.

[0029] To address the aforementioned problems, embodiments of the present invention provide a negative electrode material 10, such as... Figure 1 As shown, it includes a carbon matrix 101 and nano-silicon 102 dispersed in the carbon matrix 101. The I value of the carbon matrix 101 is greater than or equal to 400 A.U.; wherein, the I value is the peak intensity of the carbon matrix 101 at 26.5° during XRD testing.

[0030] The applicant discovered that the first efficiency of CVD silicon-carbon is composed of the first efficiency of the carbon matrix and the first efficiency of nano-silicon. The silicon first efficiency is related to the silicon grain size. The larger the silicon grain size, the higher the first efficiency. However, a large silicon grain size will seriously degrade the cycling performance. In order to ensure the cycling performance, the first efficiency of CVD silicon-carbon cannot be improved simply by increasing the silicon grain size.

[0031] In this embodiment, by designing the crystallinity of the carbon matrix 101, the I value of the carbon matrix 101 is controlled to be greater than or equal to 400 A.U., which makes the carbon substrate have good crystallinity, carbon contributes significantly during discharge, and the lithium-ion insertion / extraction efficiency is high, which can achieve efficient and reversible lithium storage. It can significantly improve the first efficiency while ensuring the integrity of the silicon-carbon composite structure, thereby improving the energy density of silicon-doped cells and meeting the urgent market demand for high-performance lithium-ion batteries.

[0032] In some embodiments, the Y value of the carbon matrix 101 is greater than or equal to 15%, wherein the Y value is the proportion of the capacity below 0.3V to the initial discharge capacity of the coin cell composed of the carbon matrix 101 after the first charge test.

[0033] In this embodiment, the first efficiency of the carbon matrix is ​​mainly reflected in the capacity contribution (Y value) below 0.3V, and the larger the Y value, the higher the first efficiency. In addition, the capacity contribution below 0.3V is strongly correlated with the crystallinity of the carbon matrix. When the Y value is greater than or equal to 15%, the carbon matrix has strong crystallinity and fewer sheet defects, which is beneficial to energy storage performance and thus helps to improve the first efficiency.

[0034] Optionally, in one embodiment, the Y value is less than or equal to 30%, which can effectively balance high initial efficiency and high energy density.

[0035] Optionally, in one embodiment, the above-mentioned I value is less than or equal to 2000 A.U., that is, the carbon matrix 101 is designed to be crystalline so that its peak intensity at 26.5° is between 400 and 2000 A.U. during XRD testing, which can further improve its first efficiency, thereby improving the first efficiency of the negative electrode material 10.

[0036] Optionally, in one specific embodiment, the above-mentioned I value is 600 to 1200 A.U., that is, the carbon substrate 101 is designed to be crystalline so that its peak intensity at 26.5° during XRD testing is between 600 and 1200 A.U., which can not only effectively improve its first efficiency, but also improve the conductivity of the carbon substrate 101, improve the overall electronic conduction efficiency of the electrode, reduce polarization loss, thereby improving the energy density utilization rate, and also avoid the problem of easy breakage when silicon volume expands due to the high brittleness of the carbon substrate 101. In other words, it can effectively balance cycle performance, energy density and the first efficiency of the negative electrode material 10.

[0037] Optionally, the I value of the carbon matrix can be increased to 400 A.U. and the Y value adjusted to 15% or higher by heat treatment at a high temperature of 800°C for 24 to 240 hours. Optionally, the heat treatment temperature is 1500 to 3200°C, which can more effectively increase the I value while ensuring the silicon matrix structure.

[0038] Optionally, after heat treatment at 800°C or higher for 24-240 hours, 50% by mass of silicon is deposited on the carbon matrix at 480°C. Then, an acetylene carbon source is introduced at 480°C for carbon coating for 6 hours to obtain silicon-carbon material. The silicon-carbon material is then assembled into a button cell and subjected to the first charge-discharge test to obtain a Y value greater than or equal to 15%.

[0039] Optionally, in one specific embodiment, the carbon matrix 101 is selected from at least one of resin-based, biomass-based, and petroleum coke-based materials, which facilitates crystallization design and makes it easy to adjust its peak intensity at 26.5° to 600-1200 A.U. during XRD testing.

[0040] Optionally, in one specific embodiment, the particle size of the carbon matrix 101 is 5 to 10 μm, which can avoid the degradation of its fast-charging performance due to the long diffusion path caused by the carbon matrix 101 being too large. For example, the particle size of the carbon matrix 101 can be any value or a range of any two of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm.

[0041] Optionally, in one embodiment, the negative electrode material 10 provided in this application has a mass fraction of 10% to 80% for nano-silicon 102 and a mass fraction of 20% to 90% for carbon matrix 101, which enables the battery to have a high capacity and good cycle performance.

[0042] Optionally, in one specific embodiment, in the negative electrode material 10 provided in this application, the mass fraction of the above-mentioned nano-silicon 102 is 30% to 50%, and correspondingly, the mass dispersion of the carbon matrix 101 is 50% to 70%. Under the premise of ensuring that the carbon matrix 101 can effectively buffer the volume expansion of silicon, thereby significantly improving cycle stability, the silicon material can be fully used to improve the energy density and capacity of the battery, and improve the overall performance of the battery.

[0043] Optionally, in one specific embodiment, the aforementioned nano-silicon 102 is silicon particles with a particle size of 0-2 nm. The particulate nano-silicon 102 can be fully dispersed in the carbon matrix 101, thereby utilizing the highly crystalline carbon matrix 101 to uniformly buffer its volume expansion and improve cycle stability. However, excessively large silicon grains will degrade cycle performance. By setting the nano-silicon 102 to silicon particles with a particle size of 0-2 nm, the first-stage efficiency of the negative electrode material 10 can be effectively improved while ensuring cycle performance, thereby increasing the cell energy density.

[0044] In this embodiment, by designing the crystallinity of the carbon matrix 101, the I value of the carbon matrix 101 is controlled to be greater than or equal to 400 A.U. and the Y value is greater than or equal to 15%, so that after the first charge test, the proportion of the capacity above 0.8V to the first discharge capacity of the coin cell assembled from the silicon-carbon anode material 10 is greater than or equal to 84%. Carbon makes a significant contribution during the discharge process, and the lithium-ion insertion / extraction efficiency is high, which can achieve efficient and reversible lithium storage. The first efficiency can be significantly improved while ensuring the integrity of the silicon-carbon composite structure.

[0045] This application also proposes a method for preparing a negative electrode material, comprising steps 201 to 202:

[0046] Step 201: Heat-treat the carbon source at a temperature of 800°C or higher for 24h to 240h to obtain a carbon matrix.

[0047] In this step, the crystallinity of the carbon source can be modified by heat treatment at a high temperature of ≥800℃ for 24h to 240h in a graphitization furnace or similar setting, resulting in a carbon matrix with better crystallinity, which facilitates lithium ion insertion / extraction and enables efficient and reversible lithium storage.

[0048] Optionally, the high-temperature heat treatment is stable at 1500–3200℃, which can more effectively improve crystallinity while ensuring the silicon matrix structure.

[0049] Step 202: Deposit nano-silicon on the surface of the silicon substrate to obtain the negative electrode material.

[0050] In this step, nano-silicon is deposited on the surface of a silicon substrate by means of chemical vapor deposition, etc., to obtain the above-mentioned silicon-carbon anode material.

[0051] In this embodiment, by heat-treating the carbon source at a temperature of ≥800°C for 24h to 240h, the crystallinity of the carbon matrix is ​​designed, and the I value of the carbon matrix can be controlled to be ≥400A.U., resulting in better crystallinity of the carbon substrate. Carbon makes a significant contribution during discharge, and the lithium-ion insertion / extraction efficiency is high, enabling efficient and reversible lithium storage. This can significantly improve the first-stage efficiency while ensuring the integrity of the silicon-carbon composite structure, thereby increasing the energy density of silicon-doped cells and meeting the market's urgent demand for high-performance lithium-ion batteries.

[0052] In the embodiments of this application, the carbon source is selected from at least one of resin-based, biomass-based, and petroleum coke-based materials.

[0053] In this embodiment, the mass fraction of nano-silicon in the negative electrode material can be controlled by adjusting the pore volume of the carbon source. Optionally, the pore volume of the carbon source can be 0.3–1.3 cm³. 3 / g.

[0054] This application also proposes a secondary battery, including a negative electrode sheet, wherein the negative electrode sheet includes a negative current collector and a negative active material layer disposed on the negative current collector, the negative active material layer including the negative electrode material as described above. The secondary battery includes a lithium-ion secondary battery.

[0055] In the secondary battery provided in this application embodiment, the negative electrode sheet further includes a conductive agent and a binder; optionally, the conductive agent includes one or more of conductive carbon black, acetylene black, Ketjen black, and carbon nanotubes, and the binder includes carboxymethyl cellulose-based binder and resin-based binder.

[0056] Optionally, in one embodiment, the carboxymethyl cellulose-based adhesive includes one or more of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose; and / or, the resin-based adhesive includes one or more of styrene-butadiene rubber, polyacrylic acid, and polyacrylonitrile.

[0057] In some embodiments, the negative electrode sheet is prepared as follows: the components used to prepare the negative electrode sheet, such as the negative electrode active material, binder and conductive agent, are dispersed in a solvent such as deionized water to form a negative electrode slurry; the negative electrode slurry is coated on both sides of a negative electrode current collector such as copper foil; after baking, rolling, cutting and other processes, the negative electrode sheet can be obtained.

[0058] The secondary battery provided in this application embodiment also includes a positive electrode, a separator, and an electrolyte.

[0059] The aforementioned positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer includes a positive active material, which may include lithium-ion transition metal oxides, ternary positive electrode materials, etc. The aforementioned lithium-ion transition metal oxide includes at least one of lithium cobalt oxide, lithium manganese oxide, and lithium iron phosphate. The aforementioned ternary positive electrode material may specifically be a high-nickel layered ternary positive electrode material.

[0060] Optionally, in one embodiment, the positive electrode further includes a conductive agent, which may include at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, hard carbon, carbon fiber, and carbon microspheres.

[0061] In some embodiments, the positive electrode sheet is prepared as follows: the components used to prepare the positive electrode sheet, such as the positive active material including the above-mentioned positive electrode material, binder and conductive agent, are dispersed in a solvent such as N-methylpyrrolidone to form a positive electrode slurry; the positive electrode slurry is coated on a positive electrode current collector such as aluminum foil; after drying, rolling, die cutting and other processes, the positive electrode sheet can be obtained.

[0062] In this embodiment, the electrolyte acts as a conductor of ions between the positive and negative electrodes. The electrolyte can be liquid, gel-like, or entirely solid. In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent, wherein the electrolyte salt is a lithium salt.

[0063] In practical applications, the negative electrode sheet, positive electrode sheet, and separator are wound together to obtain a core, the core is packaged to obtain a dry cell, and the dry cell is baked and then injected with electrolyte, formed, resealed, and sorted to obtain the above-mentioned secondary battery.

[0064] This application also proposes an electrical device, which includes the aforementioned secondary battery, serving as the power supply for the electrical device.

[0065] In practical applications, the aforementioned electrical equipment can be vehicles, etc.

[0066] It should be noted that, in the embodiments of this application, the types of vehicles include, but are not limited to, pure electric vehicles and hybrid vehicles.

[0067] For the above-described secondary battery embodiments and electrical device embodiments, the negative electrode sheet includes a negative electrode active material layer, which includes the aforementioned negative electrode material and can achieve the same technical effect. To avoid repetition, it will not be described again here. For relevant details, please refer to the description of the negative electrode material embodiments.

[0068] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application.

[0069] The present application will be described in detail below through embodiments.

[0070] Example 1

[0071] (1) Preparation of negative electrode materials

[0072] The pore volume is 0.8cm 3 / g of resin carbon matrix was subjected to high-temperature heat treatment in a graphitization furnace at 800℃ for 96h to obtain resin-based carbon matrix material.

[0073] 5 kg of carbon matrix material with an average particle size of 6 μm was placed in a fluidized bed device and deposited at 550 °C for 6 h using silane gas with a flow rate of 10 L / min under normal environmental conditions. After carbon coating treatment for 6 h, the negative electrode material was obtained.

[0074] (2) Preparation of negative electrode sheet

[0075] Conductive agent SuperP, thickener sodium carboxymethyl cellulose (CMC), binder styrene-butadiene rubber latex (SBR), and hard carbon were mixed in a mass ratio of 0.06:1.3:2:1 and stirred at 1200 rpm / min for 2 hours. The mixture was then stirred at 500 rpm / min until homogeneous. 95.64 parts of the above negative electrode material were added, and the mixture was dispersed three times at 2500 rpm / min for 90 seconds each time to prepare a lithium-ion battery negative electrode slurry. Then, 200 g / m³ of the slurry was prepared. 2 After coating both sides of the copper foil used for current collector, the negative electrode sheet is prepared by baking, rolling, and cutting, with the compaction density controlled at 1.65 g / cm³. 3 .

[0076] (3) Preparation of positive electrode sheet

[0077] LiNi nickel cobalt manganese ternary material LiNi 0.8 CO 0.1 Mn 0.1 O2, conductive agent SuperP, binder PVDF, and carbon nanotubes (CNTs) were mixed uniformly at a mass ratio of 97.6:0.8:1:0.6 to prepare a lithium-ion battery positive electrode slurry, and then 200g / m 2 After the coating amount is applied to both sides of the copper foil used for current collector, the positive electrode sheet is prepared by baking, rolling, and cutting.

[0078] (4) Preparation of electrolyte

[0079] An organic solvent was prepared by mixing ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC), and vinylene carbonate (VC) in a mass ratio of 0.3:0.3:0.3:0.07:0.03. Lithium hexafluorophosphate was then dissolved in the organic solvent to prepare the electrolyte; wherein the concentration of lithium hexafluorophosphate was 1 mol / L.

[0080] (5) Preparation of secondary batteries

[0081] The prepared positive electrode sheet, separator (PP separator) and negative electrode sheet are stacked in sequence, with the separator in the middle of the positive and negative electrode sheets. After winding, hot pressing and shaping, and electrode tab welding, a bare cell is obtained. The bare cell is placed in an outer packaging aluminum-plastic film, baked and dried, and then injected with the electrolyte prepared above. After standing, formation and capacity testing, the lithium-ion battery is completed.

[0082] Examples 2-5

[0083] The only difference from Example 1 is that in step (1), the temperature of the graphitization furnace is adjusted to 1200℃, 1600℃, 2000℃ and 3200℃ respectively.

[0084] Example 6

[0085] The only difference from Example 1 is that in step (1), the resin-based carbon matrix is ​​adjusted to a biomass-based carbon matrix.

[0086] Examples 7-8

[0087] The only difference from Example 1 is that, in step (1), the average particle size of the resin-based carbon matrix is ​​adjusted to 5 μm and 10 μm, respectively.

[0088] Examples 9-10

[0089] The only difference from Example 1 is that, in step (1), the pore volume of the carbon matrix is ​​adjusted to 0.3 cm. 3 / g and 1.3cm 3 / g.

[0090] Example 11

[0091] The only difference from Example 1 is that, in step (1), the silane gas deposition temperature is adjusted to 590°C.

[0092] Comparative Example 1

[0093] The only difference from Example 1 is that the graphitization furnace temperature was adjusted to 600°C (so that the I value of the carbon matrix was 100 A.U.).

[0094] Test example:

[0095] 1) The carbon matrix materials prepared in the above embodiments and comparative examples were subjected to I-value testing. The testing method was as follows: 2g of material was placed in a 0.5mm deep XRD sample cell at room temperature, flattened with a glass slide, and loaded into the XRD equipment. The initial test angle was set to 20°, the final test angle to 65°, the step size to 0.01°, and the angle measurement rate to 10° / min. The test data were plotted with peak intensity as the Y-axis and angle as the X-axis. The peak at 26.5° was processed. A line was drawn connecting the peak values ​​at 20° and 35°. A perpendicular line was drawn from the 26.5° point to the connecting line. The height of the perpendicular line corresponding to the Y-axis scale data is the I-value. The test results are shown in Table 1. The calculation process of the I-value of the carbon matrix material in Example 1 is as follows: Figure 2 As shown.

[0096] 2) The negative electrode, electrolyte, and lithium sheet prepared in the above embodiments and comparative examples were assembled into coin cells for coin cell testing. The testing method was to calculate the charging / discharging capacity at Y=0.3V and the charging / discharging capacity at ICE=0.8V. The test results are shown in Table 2. The coin cell preparation steps are as follows:

[0097] Assemble a negative electrode layer, a separator layer, and a lithium sheet layer in sequence, inject 10g of liquid, and let stand for 24 hours.

[0098] 3) The energy density of the lithium-ion batteries prepared in each embodiment and comparative example was tested, and the test data are shown in Table 2; the test method was as follows:

[0099] ① The electrochemical device is charged to the upper limit voltage of 1.5V at a constant current and constant voltage of 0.05C;

[0100] ② Let stand for 30 minutes;

[0101] ③ Discharge to 0.05V with a current of 0.1C and record the discharge capacity D1 of the electrochemical device.

[0102] 4) The lithium-ion batteries prepared in each embodiment and comparative example were subjected to battery cycle stability tests. The test data are shown in Table 2. The test method is as follows:

[0103] ① Charge the battery to 1.5V at a constant current of 0.05C and record the initial charge capacity C1;

[0104] ② Let stand for 5 minutes;

[0105] ③ Discharge at a constant current of 0.05C to 0.05V, and record the initial discharge capacity D1;

[0106] ④ Calculate the initial coulomb efficiency = D1 / C1.

[0107] 5) The lithium-ion batteries prepared in each embodiment and comparative example were subjected to battery cycle stability tests, and the test data are shown in Table 2; the test method is as follows:

[0108] At 25°C, lithium-ion batteries are charged and discharged at 1C / 1C within a voltage range of 0.05 to 1.5V until the capacity of the lithium-ion battery is less than 80% of the initial capacity. The number of cycles of the lithium-ion battery is recorded to characterize the cycle performance of the battery, with the unit being cycles.

[0109] The negative electrode material formulations and battery cycle stability of each embodiment and comparative example are shown in Table 1.

[0110] Table 1

[0111]

[0112] The batteries prepared in each embodiment and comparative example were subjected to cycle performance tests, and the test data are shown in Table 1.

[0113] As can be seen from the comparison of the various embodiments and comparative examples in Table 1, the CVD silicon-carbon material obtained by adopting the carbon matrix crystallization scheme of the present application has higher first-efficiency and can improve the cycle performance and discharge capacity of the battery.

[0114] In summary, in this embodiment, by designing the crystallinity of the carbon matrix, controlling the I value of the carbon matrix to be greater than or equal to 400 A.U. and the Y value to be greater than or equal to 15%, carbon makes a significant contribution during discharge, resulting in high lithium-ion insertion / extraction efficiency and enabling efficient and reversible lithium storage. This significantly improves the first-stage efficiency while ensuring the integrity of the silicon-carbon composite structure, thereby increasing the energy density of silicon-doped cells and meeting the market's urgent demand for high-performance lithium-ion batteries.

[0115] Although preferred embodiments of the present invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present invention.

[0116] The present invention has provided a detailed description of a negative electrode material, a secondary battery, and an electrical device. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, those skilled in the art will recognize that there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A negative electrode material (10), characterized in that, The negative electrode material (10) includes a carbon matrix (101) and nano-silicon dispersed in the carbon matrix (101), wherein the I value of the carbon matrix (101) is greater than or equal to 400 A.U.; Wherein, I value is the peak intensity of the carbon matrix (101) at 26.5° during XRD testing.

2. The negative electrode material (10) according to claim 1, characterized in that, The I value is 600–1200 A.U.

3. The negative electrode material (10) according to claim 1 or 2, characterized in that, The carbon matrix (101) is selected from at least one of resin-based, biomass-based, and petroleum coke-based materials.

4. The negative electrode material (10) according to any one of claims 1 to 3, characterized in that, The carbon matrix (101) has a particle size of 5–10 μm.

5. The negative electrode material (10) according to any one of claims 1 to 4, characterized in that, The mass fraction of the nano-silicon is 10% to 80%.

6. The negative electrode material (10) according to claim 5, characterized in that, The mass fraction of the nano-silicon is 30% to 50%.

7. The negative electrode material (10) according to any one of claims 1 to 6, characterized in that, The nano-silicon is silicon particles with a particle size of 0 to 2 nm.

8. The negative electrode material (10) according to any one of claims 1 to 7, characterized in that, The Y value of the carbon matrix (101) is greater than or equal to 15%; wherein, the Y value is the proportion of the capacity below 0.3V of the coin cell composed of the carbon matrix (101) to the initial discharge capacity after the first charge test.

9. A secondary battery, comprising a negative electrode, characterized in that, The negative electrode sheet includes a negative current collector and a negative active material layer disposed on the negative current collector, wherein the negative active material layer includes the negative electrode material (10) as described in any one of claims 1 to 8.

10. An electrical appliance, characterized in that, The device includes the secondary battery as described in claim 9, wherein the secondary battery serves as the power supply for the electrical equipment.

11. A method for preparing a negative electrode material, characterized in that, include: The carbon source is heat-treated at a temperature of 800°C or higher for 24 to 240 hours to obtain a carbon matrix. Nano-silicon is deposited on the surface of the silicon substrate to obtain the negative electrode material.